Prevalence study of violence and abuse against older women - Alves, José Ferreira (2011)
The Portuguese prevalence survey of violence against older women was conducted through a cross-sectional design and aimed at five broader goals: 1. Provide estimates of the prevalence of self-reported mistreatment in a national sample of dwelling women aged 60 years and older. The mistreatment concept encompasses neglect, and five types of abuse: emotional, financial, physical, sexual and violation of personal rights 2. Identify the perpetrators of the several forms of mistreatment. 3. Describe variables pertaining the women psychological, social and demographic con-text and background and identify the possible relation between those variables and the mistreatment: risk factors from a meso and macro level. 4. Describe the disclosure and the reasons for not disclosing the mistreatement to both personal and professional contacts. 5. Describe the self-reported psychological and emotional consequences of the mi-streatment.